The criminalization of medicine: America's war on doctors - Libby, Ronald T. (Praeger series on contemporary health and living, 2008)
Decline in the status of doctors: the tragic case of Dr. Benjamin Moore -- Medical McCarthyism -- Prosecuting doctors: sexual harassment and creating crimes -- Judicial prejudice, state terrorism, and forced medication: the cases of Jeffrey J. Rutgard, M.D., George O. Krizek, M.D. and Charles T. Sell, D.D.S. -- Prosecutorial overreach: anti-kickback laws and the "Pinellas 14" -- DEA drug warriors: targeting doctors as drug dealers -- Witch-hunt for "drug-dealing" doctors: James Graves, M.D., and Frank Fisher, M.D. -- DEA show trial: "magical moments" and the comprehensive care conspiracy